ANALISIS UPAYA ORANG TUA DALAM MENDIDIK ANAK DIMASA PANDEMI - Siti Maryam Munjiat (Risâlah, Jurnal Pendidikan dan Studi Islam, 2020)
Abstract This study aims to analyze the efforts of parents in educating children during the covid-19 pandemic. Covid-19 pandemic makes it difficult for teachers, parents and students to carry out education. Therefore, in order to avoid the distance between the teacher, parents and students, the purpose of the research is carried out. The research method used is library research or library research by collecting journals, books and previous research results that are relevant to the above theme. The results of this study are: 1) Time management; manage work time and time to educate children. 2) Occasionally invite children to discuss about problems experienced in doing learning, 3) Be uswah/ model for children, do good things in front of children. 4) Accompany children when learning online, 5) In order not to be bored, do positive things with children, such as raising birds, planting trees and others. 6) Pray for children especially after praying, Keywords: Pandemic periode, Parents’ effort, Educating children